Integrating epigenetic modification and stem cell therapy strategies: A novel approach for advancing Alzheimer’s disease treatment − A literature review - Widaja, Edhijanto; Pawitan, Jeanne A. (Narra Sains Indonesia, 2024)
Alzheimer's disease (AD) is the most frequent form of dementia and represents an increasing global burden, particularly in countries like Indonesia, where the population has begun to age significantly. Current medications, including cholinesterase inhibitors and NMDA receptor antagonists, have modest effects on clinical symptoms in the early to middle stages, but there is no curative treatment available so far despite progress. Activating or repressing epigenetic modifications, including DNA methylation, histone modification and microRNA regulation, appears to play an important role in AD development. These alterations further enact transcriptional changes relevant to the signature AD pathologies of amyloid-β deposition, tau protein malfunctioning, neuroinflammation, and neuronal death. Here, we discuss the feasibility of targeting these epigenetic alterations as a new treatment strategy due to the reversibility of epigenetics and their ability to correct faulty gene expression. We also review the combined promise of stem cell therapies and epigenetic modulation in neurodegeneration, inflammation and cognitive decline. This combined approach may provide a multifaceted strategy to slow disease progression, replace lost neurons, and restore neural function. Despite challenges, including ethical, financial, and methodological barriers, ongoing research in epigenetic modulation and stem cell therapy holds promise for pioneering therapies in AD.